Reading partner in promoting reading habits - Norazizan, Muhammad Hafidzudeen; Choong, Angelyn Ern Nie; Mohammad Baba, Munifah (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
Reading habits as well as motivation to read are popular topics research in the field of education. Scholars and academicians have studied numerous techniques and ways in promoting and nurturing reading habits among children, adolescents and adults. New ways of encouraging and increasing the motivation to read has been presented in research and studies due to the changing learning approaches in education to suit the current learning styles. The new age of technology also affects the reading habits among children as the non-stop birth of technology make the reading experience different, paperless and more interactive. In parallel of the birth of technology, reading habits are getting less attention as students are spending more time on technology. Realizing the importance of reading habits and it effects to literacy and language development, research has been conducted in the education field in the hope that it would benefit educators and stakeholders. This conceptual paper is looking at a way in promoting reading habits which is by having a reading partner. This paper also provides a brief literature review of articles, journals, books and other academic sources. The advantages and problem of reading partner also is also discussed. The authors also give recommendations as well as suggestions for the use of having reading partners in promoting reading habits.